Fracture analysis of multiple curved cracks in an orthotropic FGM coating bonded to an orthotropic substrate layer. (17th February 2023) - Moradi, I.; Monfared, M.M.
Highlights: Mixed mode SIFs for multiple curved cracks in an orthotropic FGM layer bonded to an orthotropic layer are determined. The method allows considering any number of curved cracks namely circular arc and parabolic crack. The elastic properties of the FGM layer are assumed to vary exponentially along the thickness of the layer. Fourier transform is used to solve the edge dislocations. The problem is formulated in terms of singular integral equations by means of distributed dislocation technique (DDT). Abstract: In this paper, based on the distribution dislocation technique (DDT), multiple curved cracks placed in an orthotropic FGM layer bonded to an orthotropic layer and also interface cracks are considered. With the use of integration of Fourier transform the problem is reduced to a system of Cauchy-type singular integral equations which are solved numerically to compute the dislocation density on the surfaces of the cracks. The distribution dislocation is a powerful method to calculate accurate solutions to plane crack problems; especially this method is very good for solutions of curved crack patterns. Hence this technique allows considering any number of embedded and edge cracks with arbitrary curved shape and also interface cracks. Many numerical examples are given to validate our results with available analytical, finite element and experimental methods. The primary objective of this paper is to investigate the effects of the interaction of multiple curved cracks, the shape of crack, material orthotropy, nonhomogeneity parameters, the thickness ratios and the crack length on the modes I and II SIFs and energy release rate. Numerical results show that the normalized energy release rate and modes I/II SIFs decreasing with the both of the stiffness ratio of the coating and the nonhomogeneity parameter.